Education Model for Environmental Living Environment Based on Local Genius for Elementary School Students Who Lived in Peatland - ., Tonich; Pisi, Berkat A. (American Journal of Social Sciences and Humanities, 2019)
The lack of studies on children’s education in peatlands in Kalimantan, Indonesia, inspires researchers to examine in depth about the various local wisdoms that must be internalized to future generations. The purpose of this study is to understand the various local wisdoms that exist in peatland communities, which can be transmitted and preserved through education to elementary school age children. The method used in this research is qualitative research, with a grounded research approach. The study was conducted in the Kalampangan sub-district, Sabangau sub-district, Palangka Raya City in January-August 2019. Data were collected through in-depth interviews and participatory observation. The validity of the data is obtained by prolonging the stay at the study site, using data triangulation, both checks, checks, and crosses. Data were analyzed using four steps ranging from data collection, data reduction, data classification, and drawing conclusions. The results of the data analysis show that: 1) a lot of local parish can be internalized to elementary school-age children in preserving peatlands, such as not burning peat, not hurting peat soil, using peat wisely, and keeping peat friendly, 2) local wisdom values that can be learned by elementary school children are, the value of independence living in peat areas is, the value of creativity, the value of love for the environment, cultural values, the value of togetherness or values of mutual cooperation, the values never give up with the state of the natural environment , and the value of independence.